Description of Alternative Approaches to Measure and Place a Value on Hospital Products in Seven OECD Countries - Lorenzoni, Luca (OECD Health Working Papers, 2011)
This paper provides a description of the classification systems used to measure hospital services in selected OECD countries: Australia, Canada, France, Germany, Norway, United Kingdom (England), and the United States. Three classifications are relevant: those on diagnoses; on procedures; and on products. In addition, methods used to measure the cost of hospital services are reviewed